Model of the Relationship Between Selected Soil Physical Properties of Oil Palm Soil - Bandi Hermawan; Elsa Lolita Putri; Wanda Afrilia Utami; Priyono Prawito (UNIVERSITY OF LAMPUNG, 2026)
Soil, water, and plants are interrelated elements in agricultural production. An in-depth understanding of the characteristics and interactions of these three aspects is essential in effective agricultural system management. The study aims to examine the relationship between soil’s water-holding capacity and different land-slope levels and to identify the physical soil characteristics that affect it. The research was conducted in a community oil palm plantation in Talang Tengah I Village, Pondok Kubang District, Central Bengkulu Regency, Bengkulu Province. The method used was a survey with purposive sampling across five slope levels: flat (0-8%), sloping (8-15%), slightly steep (15-25%), steep (25-45%), and very steep (45-100%). The data were statistically analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with WarpPLS 7.0. The results showed that slope had a significant effect on various soil physical characteristics and soil water holding capacity. The steeper the slope, the greater the decrease in soil permeability, total pore space, and soil organic carbon, and the greater the increase in soil volume weight, which results in a decrease in soil water holding capacity. The resulting model shows agreement in describing the relationships between variables: slope affects organic matter, sand %, and permeability, and volume weight affects total pore space and permeability, which in turn affects the soil’s capacity to hold water.